(untitled) (Revista científica Olimpia, 2021)
The work it constitute necessary propose to resolve the didactic and methodological point of view one of the principals problems of the physical education nowadays in the High Education, has a principal objective stipulate aspects in theorist order about the workout of physical exercising just like the implication of impulsive operations and cognitive in the individual mobilization must made to execute a task, physical mechanism and mental that this person must put in game, this will determine all the physical work. The main results must be in theorist aspects, which considered this planed app of the contents in individual character and systematic for the knowledge in workout of physical exercising of compensation of the mental working has a part of discipline program Physical Education Plan E.